Asymmetric Heterogeneous Catalysis by Nanoporous Materials Using Privileged Ligands as Chiral Building Blocks - Silva, Ana R.
Asymmetric catalysis is unique in the sense that a minute quantity of a chiral catalyst is sufficient to produce large amounts of the desired chiral product [1]. With the increased demand for chiral products a number of efficient asymmetric homogeneous catalysts based on transition metal complexes with versatile chiral privileged ligands have been developed that work for a wide range of organic reactions. Their application in industry has been however hindered by their high cost and the product metal contamination issue. The immobilization of asymmetric homogeneous catalysts on porous supports has been a quite explored strategy to make them recyclable and economical. More recently, the construction of innovative hybrid porous materials such as MOFs and PMOs using a modular approach starting from conveniently di-derived chiral privileged ligands has been a reliable strategy to prepare efficient asymmetric heterogeneous catalysts with higher metal loadings than the post-synthetic techniques. The privileged ligands that have been used as MOFs or PMOs chiral building blocks are the BI-NOL/BINAP, salen and bis(oxazoline). Herein focus will be given to the bis-functionalized chiral privileged ligands which have been used to synthesize this innovative nanoporous materials and the outcome of their application as asymmetric heterogeneous catalysts in organic transformations.